Patients with Obstructive Sleep Apnea Have Altered Levels of Four Cytokines Associated with Cardiovascular and Kidney Disease, but Near Normal Levels with Airways Therapy - Wang Y; Meagher RB; Ambati S; Cheng H; Ma P; Phillips BG (Nature and Science of Sleep, 2021)
Ye Wang,1 Richard B Meagher,2 Suresh Ambati,2 Huimin Cheng,1 Ping Ma,1 Bradley G Phillips3 1Department of Statistics, University of Georgia, Athens, GA, 30602, USA; 2Department of Genetics, University of Georgia, Athens, GA, 30602, USA; 3Clinical and Administrative Pharmacy, Clinical and Translational Research Unit, University of Georgia, Athens, GA, 30602, USACorrespondence: Richard B Meagher Tel +1 706 296 9966Email meagher@uga.eduIntroduction: Obstructive sleep apnea (OSA) results in chronic intermittent hypoxia leading to systemic inflammation, increases in pro-inflammatory cytokines TNF-Alpha and IL-6, and increased risk for a number of life threatening medical disorders such as cardiovascular and kidney disease.Methods: A BioPlex Array was used to examined the serum levels of four cytokines also expressed in endothelial cells and/or macrophages and associated with cardiovascular and kidney disease risk.Results: Relative to untreated OSA patients, airways treated OSA patients had a 5.4-fold higher median level of MMP2 (p = 9.1x10− 11), a 1.4-fold higher level of TWEAK (p = 1.8x10− 7), a 1.7-fold higher level of CD163 (p = 1.4x10− 6), but a 2.0-fold lower level of MMP3 (p = 7.9x10− 7). Airway treatment resulted in levels more similar to or indistinguishable from control subjects. Both t-SNE or UMAP analysis of the global structure of these multi-dimensional data revealed two data clusters, one populated primarily with data for controls and most airways treated OSA patients and a second populated primarily with data for OSA patients.Discussion: We discuss a concept in which the aberrant levels of these cytokines in untreated OSA patients may represent a chronic response after years of experiencing intermittent nightly hypoxia, which attenuated the acute response to hypoxia. A balanced therapeutic correction of the aberrant levels of these cytokines may limit the progression of CVD and kidney disease in OSA patients.Keywords: CPAP, OSA, atherosclerosis, cytokines, renal disease, apnea